Cox2 Inhibitor Test Of Limpasu (Baccaurea Lanceolata) Using Computation Method - Samsul Hadi; Nashrul Wathan; Deni Setiawan; Pratika Viogenta; Kunti Nastiti (Institute Of Computer Science (IOCS), 2023)
The use of anti-inflammatory drugs with the COX-2 method is starting to develop tolerance, so that drugs circulating in the community now cause various kinds of complaints, namely inhibition of blood clotting and stomach ulcers. Therefore, the purpose of this study was to screen natural product compounds that have potential as COX-2 inhibitors. The materials used are compounds contained in B.lanceolata and COX-2 enzymes with code 3ln1 obtained from the RCSB database, the equipment used is a windows laptop with PLANT and discover studio software, the method used in this study is a computational study using docking software . The results in this study were that the docking score of B. lanceolata was higher than the native ligand, so the effectiveness was weaker than the native ligand, the docking scores obtained were as follows: Epidihydrotutin (-50.243); Sapidolide A (-51052); Melatonin (-53039); 6'-O-Vanilloylisotachioside (-60.910) and 6'-O-Vanilloyltachioside (-61.131). In conclusion, 6'-O-Vanilloyltachioside is a potential compound as a COX-2 inhibitor from B.lanceolata.